Faktor – Faktor Yang Berpengaruh Terhadap Pemilihan Moda Kereta Bandara Adi Soemarmo Solo - Priyanto, Sapto (Politeknik Perkeretaapian Indonesia Madiun, 2018)
The Government through the National Railway Master Plan has launched the development of the Airport Railway Network and Services to facilitate passenger mobility, one of which is the construction of the Adi Soemarmo Airport train. In April 2017 a groundbreaking project for the development of the Adi Soemarmo Airport, Boyolali District by the President of the Republic of Indonesia was scheduled to be operational in 2019. This study uses a discrete choice model to express the opportunities of each passenger to use the airport train. The research instruments were prepared using predictor variables developed from service dimensions according to Gaspers. The sample used was 200 respondents with random sampling techniques. The data collected is processed using a binary logical regression model because the response variable is in the form of a dichotomy. The results showed the accuracy of the train schedule and affordability of train fares affect the willingness to use airport trains.